2016
DOI: 10.1653/024.099.sp117
|View full text |Cite
|
Sign up to set email alerts
|

Developing Field Cage Tests to Measure Mating Competitiveness of Sterile Light Brown Apple Moths (Lepidoptera: Tortricidae) in Western Australia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…New proposed targets of SIT emerge slowly, against a background where the SIT has been well developed and deployed against only a small range of pest species of Diptera and Lepidoptera [23]. Despite radiation biology being known regarding a large range of species in these orders, the results have not been translated into many field programs [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New proposed targets of SIT emerge slowly, against a background where the SIT has been well developed and deployed against only a small range of pest species of Diptera and Lepidoptera [23]. Despite radiation biology being known regarding a large range of species in these orders, the results have not been translated into many field programs [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The competitive fitness of sterile and wild insects is critical for success, and often short-term mating experiments can be used to determine whether sterile insects participate proportionally [23,24,25]. Multiple mating and longevity of weeks by BMSB meant that we needed another approach to assess fitness, so we compared the level of egg sterility observed from cages, with an over-flooding ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Standard field cage tests routinely used to measure the sexual competitiveness of factory-reared tephritid fruit flies were validated and adapted for moths (LBAM as model species). The results indicated that sterile-male-only releases have the potential to increase the mating competitiveness of the released irradiated moths, but this conclusion requires additional experiments for confirmation [136].…”
Section: Quality Control For Lepidoptera Sit or Ismentioning
confidence: 99%
“…The use of field cages to assess mating performance and competitiveness of pest insects has gained in importance during the last decade. These cages were originally designed for testing the mating behavior of fruit flies (Drosophilidae) [ 26 , 27 ], but their use has been expanded to tsetse flies [ 21 , 22 , 28 , 29 , 30 , 31 , 32 ], mosquitoes [ 33 , 34 ] and Lepidoptera [ 35 , 36 , 37 , 38 ]. Walk-in field cages have proved to be good substitutes for field studies that are more complex and expensive with many parameters that cannot be controlled.…”
Section: Introductionmentioning
confidence: 99%